2019
DOI: 10.1128/jvi.00998-19
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Activation of Lytic Epstein-Barr Virus Gene Expression without Virion Production

Abstract: Several therapeutic strategies targeting Epstein-Barr virus (EBV)-associated tumors involve upregulation of viral lytic gene expression. Evidence has been presented that the unfolded protein response (UPR) leads to EBV lytic gene expression. Clofoctol, an antibacterial antibiotic, has been reported to upregulate the UPR in prostate cancer cell lines and to slow their growth. We investigated the effects of clofoctol on an EBV-positive Burkitt lymphoma cell line and confirmed the upregulation of all three branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…We have used GFP expression by the BX1 cell line as an indicator of lytic gene expression in this and several previous investigations [ 12 , 26 ]. GFP expression is appreciated in only a small percentage of cells under basal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have used GFP expression by the BX1 cell line as an indicator of lytic gene expression in this and several previous investigations [ 12 , 26 ]. GFP expression is appreciated in only a small percentage of cells under basal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent work, we reported that eIF2α phosphorylation, by the protein kinase R (PKR)-like endoplasmic reticulum (ER) kinase (PERK), activated EBV lytic viral transcription [ 12 ]. Phosphorylation of eIF2α has been extensively studied in other contexts [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasome inhibitor such as bortezomib and endoplasmic reticulum (ER) stress inducers such as thapsigargin and tunicamycin, on the other hand, can induce EBV lytic cycle by activating ER stress/unfolded protein response (UPR), which induces JNK and/or C/EBP-β and activates Zp through C/EBP-binding sites in ZII and ZIIIB elements [ 24 , 25 ]. UPR-induced lytic reactivation was also observed in clofoctol treatment, which mediates the activation of the PERK-XBP1 axis [ 26 ].…”
Section: Lytic Inducersmentioning
confidence: 99%
“…Indeed, a pilot study on the efficacy and safety of romidepsin in treating extranodal natural killer/T-cell lymphoma found a substantial increase in viremia in these patients [ 52 ]. The novel compound C7 [ 36 , 42 , 46 ] and anti-bacterial antibiotic, clofoctol [ 26 ], were found to induce the expression of immediately early and early lytic proteins, but not late lytic proteins. Moreover, EBV virions were not produced after lytic induction by these two compounds.…”
Section: Weaknesses and Concerns Related To The Lytic Inducing Commentioning
confidence: 99%